Maternal diet and age alter direct and indirect relationships between life‐history traits across multiple generations. (21st December 2018) - Goos, Jared M.; Swain, Cameron J.; Munch, Stephan B.; Walsh, Matthew R.
Abstract: Maternal age has important consequences for offspring fitness, with influences on size, development and reproductive schedules. Such maternal age effects may be driven by differential provisioning of resources; yet, little is known about the role of environmental supply of nutritional resources in mediating such effects. We tested the influence of limiting nutritional resource, dietary phosphorus (P), on maternal age effects across multiple generations by examining the potential interactive effects of maternal nutrition and age on daughter and granddaughter life‐history traits in the freshwater crustacean Daphnia pulicaria . Maternal age and diet had significant but contrasting effects on offspring life history. We did not observe any evidence that age effects on offspring life history are mediated by maternal diet. However, granddaughter growth and size at maturation were influenced by the interaction between grandmaternal age and diet, suggesting that the appearance of transgenerational effects of age and diet were delayed by one generation. Because offspring life history is often linked directly and/or indirectly to life history variation in previous generations, we utilized structural equation modelling (SEM) to assess such direct or indirect relationships. SEM revealed striking differences in the relationship between growth, development time and fecundity both within and among generations, depending on the age and diet in the F0 generation. Interestingly, direct and persistent relationships between the F0 generation and the F2 generation are most prevalent when grandmothers are old and fed low P diets, and such relationships are largely driven by fecundity in the F0 generation. Additionally, indirect causal relationships between the F0 generation and F2 generation are most pronounced when grandmothers are young and fed low P diets or when grandmothers are old and fed high P diets. Our results indicate that transgenerational effects of maternal age and environment persist across multiple generations, and vary between successive generations. Further, our examination of the interaction network between life‐history traits of each generation suggest that the mechanisms for such persistent transgenerational effects are highly dependent on maternal condition. A plain language summary is available for this article. Abstract : Plain Language Summary